Infrared Sensitizers in Titania‐Based Dye‐Sensitized Solar Cells using a Dimethylferrocene Electrolyte. Issue 11 (5th September 2013) - Daeneke, Torben; Gräf, Katja; Watkins, Scott E.; Thelakkat, Mukundan; Bach , Udo
<x xml:space="preserve">Abstract</x> Vide infra: Two boron‐dipyrromethene (BODIPY)‐type infrared sensitizers are investigated for use in titania‐based dye‐sensitized solar cells (DSCs). The DSCs use a solution of dimethylferrocene (Me2Fc) in nitromethane as electrolyte. The titania conduction band edge is fine‐tuned by adding lithium ions from LiTFSI, while the choice of dimethylferrocene as redox shuttle provides the ideal driving force for dye regeneration, allowing the BODIPY‐based DSCs to reach unprecedented quantum efficiencies in the near‐infrared.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>